Antimicrobial Activities against Periodontopathic Bacteria of Pittosporum tobira and Its Active Compound - Hoàng, Việt Bách Khoa (MDPI, 2022)
The study of medicinal plants for treatment of periodontitis is of great value to establish their efficacy as sources of new antimicrobial drugs. Five hundred and fifty eight Korean local plant extracts were screened for antibacterial activity against representative periodontopathic bacteria such as Porphyromonas gingivalis, Prevotella intermedia, and Fusobacterium nucleatum. Among the various medicinal plants, the alcohol extract of Pittosporum tobira, which significantly exhibited antibacterial effect for all tested strains, showed the highest activity in the antimicrobial assays. NMR analyses revealed that R1-barrigenol, a triterpene sapogenin, was the most effective compound in P. tobira. These results demonstrated that P. tobira possesses antimicrobial properties and would be beneficial for the prevention and treatment of periodontitis.